Model Authentic Assessment dalam Pembelajaran Sastra Terintegrasi Karakter Multikultural - Sri Wahyuni; Ari Ambarwati; NFN Junaidi; Junaidi Ghony; Zulkifli Osman (JENTERA: Jurnal Kajian Sastra, 2022)
Character education, incredibly multicultural characters, must be instilled in students significantly to minimize conflict in a society, including the plural and heterogeneous Indonesian society. Planting multicultural characters, especially in academic learning, can be done by integrating these characters in the learning and assessment process. The research goals to develop an assessment activity and an authentic assessment instrument model in academic learning that integrates multicultural characters. The research method is Research and Development (R&D). The research uses ADDIE model developed by Reiser and Molley, namely Analysis, Design, and Development. The results of the research formulates two findings, first, the model of assessment activities in literary learning that integrates multicultural characters can be done through (1) social studies of life in literary works, (2) through appreciation of literary works that contain multicultural values,(3) through role-playing in drama, (4) through a comparison of literary works, and (5) through field experience when appreciating and writing literary works. Second, the authentic assessment instrument model in academic learning that integrates multicultural characters are developed through the techniques of (1) observing multicultural attitudes, (2) self-assessment related to multicultural attitudes, (3) peer assessment related to multicultural attitudes, (4) direct questions about multicultural attitudes furthermore (5) personal reports related to multicultural attitudes. AbstrakPendidikan karakter khususnya karakter multikultural perlu dan penting untuk ditanamkan pada peserta didik terutama untuk meminimalisasi konflik pada suatu masyarakat termasuk masyarakat Indonesia yang majemuk dan heterogen. Penanaman karakter multikultural khususnya dalam pembelajaran sastra dapat dilakukan dengan mengintegrasikan karakter tersebut dalam proses pembelajaran dan asesmennya. Tujuan kajian adalah mengembangkan model kegiatan asesmen dan model instrumen authentic asessment dalam pembelajaran sastra yang mengintegrasikan karakter multikultural. Rancangan penelitian ini adalah Research and Development (R&D). Penelitian menggunakan R & D model ADDIE yang dikembangkan Reiser dan Molley yaitu analisis, desain, dan pengembangan. Hasil penelitian memformulasikan dua temuan, pertama, model aktivitas asesmen dalam pembelajaran sastra yang mengintegrasikan karakter multikultural dapat dilakukan melalui (1) kajian-kajian sosial kehidupan dalam karya sastra, (2) apresiasi karya sastra yang mengandung nilai-nilai multikultural, (3) permainan peran dalam drama, (4) perbandingan karya sastra, dan (5) pengalaman lapangan ketika mengapresiasi dan menulis karya sastra. Kedua, model instrumen authentic assessment dalam pembelajaran sastra yang mengintegrasikan karakter multikultural dikembangkan melalui teknik (1) observasi sikap multikultural, (2) penilaian diri terkait sikap multikultural, (3) penilaian antarteman terkait sikap multikultural, (4) pertanyaan langsung tentang sikap multikultural, dan (5) laporan pribadi terkait sikap multikultural.